Are the Effects of Age Still Relevant in Predicting Malaysian Investors’ Risk-Taking Behavior in Stock Market? - Lim Li Chin, Audrey; Shahzad, Arfan (International Journal of Engineering and Technology, 2018)
The role of age in moderating investor’s self-confidence bias, herding, conservatism bias, familiarity bias, and regret in risk-taking behavior is explored using data collected from retail investors in Melaka, Selangor, and Wilayah Persekutuan (W.P.) Kuala Lumpur. As indicated in data analysis by Partial Least Squares Structural Equation Modelling (PLS-SEM), age plays an important moderating role in herding, regret, and self-confidence bias in investor’s risk-taking behavior. While younger investors who tend to herd are more risk averse and feel more regret in risk-taking than the older group, older investors seem to exhibit a higher level of self-confidence bias than younger investors. However, the risk- taking distribution between the age groups indicates no significant difference. Thus, the readiness in greater levels of risk acceptance depends on the individuals’ preference towards herding, regret, and self-confidence bias. Furthermore, this study also address contradictions in the existing literatures that fuels stereotyping and discrimination based on age. Therefore, age stereotype should be avoided when formulating microstructure strategies to raise the investor’s participation in the stock market.
Keywords: Age; Risk-Taking; Herding; Conservatism; Familiarity Bias; Regret; Self-Confidence Bias